Internet of Things ESP8266 Module for Vocational High School Student - Prismahardi Aji Riyantoko; Ahmad Khairul Faizin; Burhan Syarif Acarya; Fairuz Mumtaz Idhizar Farraz (Nusantara Science and Technology Proceedings, 2022)
The development of information and communication technology in the industrial era 4.0 is very rapid, especially in the field of IoT (Internet of Things). To get data and process data very quickly and in real-time, it takes a device that is connected to the internet network that will be able to provide information to anyone who is connected to the IoT device. IoT is the development of a system that can monitor and control from a remote place via the internet. In the current era, almost all people can access the internet easily, so by utilizing and optimizing the use of communication through the internet network by connecting sensor and actuator devices to the internet network. With this development, we need to provide the community with knowledge and skills about IoT through workshops, training and mentoring. The training includes knowledge of sensors, microcontrollers, and actuators that can be programmed and connected to the internet network. The ESP8266 microcontroller is a control device that can be filled with a program for controlling and monitoring devices installed on the internet network